General Decay Stability for Stochastic Functional Differential Equations with Infinite Delay. (26th January 2010) - Liu, Yue; Meng, Xuejing; Wu, Fuke
Abstract : So far there are not many results on the stability for stochastic functional differential equations with infinite delay. The main aim of this paper is to establish some new criteria on the stability with general decay rate for stochastic functional differential equations with infinite delay. To illustrate the applications of our theories clearly, this paper also examines a scalar infinite delay stochastic functional differential equations with polynomial coefficients.